(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
This study examines higher education as a pedagogical platform for enhancing students’ media competence in the digital age. It analyzes how curriculum design, teaching methods, and digital learning environments contribute to the development of critical thinking, information literacy, and responsible media use. The research highlights the role of universities in preparing students for active participation in information-rich societies. Findings indicate that integrating media education into academic programs strengthens students’ analytical skills, communication abilities, and civic engagement in both online and offline contexts.